Associations Between Exposure and Receptivity to Branded Cigarette Advertising and Subsequent Brand Preference Among US Young Adults. Issue 6 (8th June 2019) - Moran, Meghan Bridgid; Soneji, Samir; Tan, Andy S L; Choi, Kelvin
Abstract: Introduction: Exposure and receptivity to cigarette advertising are well-established predictors of cigarette use overall. However, less is known about whether exposure and receptivity to advertising for specific brands of cigarettes (ie, Marlboro, Camel, and Newport) are longitudinally associated with any subsequent cigarette use and subsequent use of those specific brands. Methods: We analyzed data from a US sample of 7325 young adults aged 18–24 years who completed both Wave 1 and Wave 2 of the Population Assessment of Tobacco and Health study. Weighted logistic regression models were used to examine (1) among Wave 1 never-smokers, associations between Wave 1 exposure and receptivity to advertising for Marlboro, Camel, and Newport and subsequent overall and brand-specific smoking initiation at Wave 2, and (2) among Wave 1 ever-smokers, associations between Wave 1 exposure and receptivity to advertising for Marlboro, Camel, and Newport and subsequent preference of those brands at Wave 2. Results: Among Wave 1 young-adult never-smokers, exposure to Camel advertising, but not Marlboro or Newport, was associated with smoking initiation with any brand of cigarettes at Wave 2. Among Wave 1 young-adult ever-smokers, receptivity to Marlboro, Camel, and Newport advertising was associated with subsequent preference for each brand, respectively, at Wave 2. Conclusions: This study found evidence for the association between receptivity to branded cigarette marketing and subsequent use of that brand. These findings provide evidence regarding the pathways through which cigarette marketing attracts young adults to use cigarettes and can inform tobacco prevention and counter-marketing efforts. Implications: This study extends prior work on the effects of cigarette advertising exposure and receptivity by illustrating the brand specificity of this advertising. These findings provide evidence that receptivity to branded cigarette advertising is longitudinally associated with preference for those specific cigarette brands.